Analisis Survival pada Data Pasien Covid 19 di Kabupaten Jember - Audina, Bella; Fatekurohman, Mohamat (BERKALA SAINSTEK, 2020)
The confirmed number of positive Covid 19 cases in Indonesia until June 15th, 2020 was 38.227 people with 3.134 dead, case fatality rate 5,9%. Case fatality rate is the percentage of the number of dead people from all confirmed and reported positive cases . Particularly, in Jember Regency, the spreading of Covid 19 is still underway day by day with the increasing of number of patient so that appropriate preventive and treatment should be done precisely. The problem of the paper is the survival analysis of Covid 19 patient by using Kaplan Meier and Log Rank test method. The result of this paper, the result of the analysis using Kaplan Meier Curve method, patients with male sex have a chance of recovering faster compared with female patients and patients with age interval of 40-49 years have a chance of recovering faster than any other age intervals, meanwhile Log rank test did not provide significant results. So the Kaplan Meier Curve method is more appropriate to analyze Covid 19 patient data in Jember compared to the Log rank test.